The development of an intervention to manage pain in people with late-stage osteoarthritis - Tina Kruger-Jakins; Melissa Saw; Naila Edries; Romy Parker (AOSIS, 2016)
Background: Osteoarthritis (OA) is one of the most common musculoskeletal conditions worldwide, affecting the functional abilities of millions of people. Arthroplasty is recommended as a successful treatment option for late-stage OA. However, in South Africa there are extensive waiting lists for OA-related arthroplasty in government hospitals. This has negative consequences for patients having to cope for long periods of time with chronic pain and its impact. Alternative treatment methods in the form of physiotherapy-led exercise and education programmes focusing on pain, disability, self-efficacy, physical function and health-related quality of life have had good impact in populations elsewhere. Objectives: To develop an exercise and education intervention based on the current literature and by doing a field survey in a South African population. Results: A combined educational approach, with a strong focus on the physical aspects of exercise in particular, was adopted for the intervention in order to improve function and manage the disability associated with OA. Conclusion: This paper reports on the process and development of an intervention for use in South Africans with late-stage OA awaiting arthroplasty. Keywords: Hip/knee osteoarthritis, arthroplasty, joint replacement, bio-psychosocial intervention, waiting list, physiotherapy, exercise, education, chronic pain